Enhanced Perovskite Solar Cell Performance by Adding Magnesium Acetate Using Two-Step Spin-Coating Method. Issue 1 (December 2021) - Yusra, D A; Mufti, N; Muyasaroh, A F; Latifah, E
Abstract: The poor stability of perovskite materials is a problem of concern in commercialization. In this study, we investigated the doping of magnesium cations (Mg 2+ ) in PbI2 to improve the stability and efficiency of perovskite solar cells. The doping effect of Mg 2+ can increase the crystallization rate. The perovskite film fabricated structure consists of ITO/TiO2 /perovskite/CuO. The fabrication method used is a two-stage spin coating. The concentrations of MgAc2 were used 0, 0.75, 1, and 1.25 mg ml −1 . The characterizations used are XRD (X-Ray Diffraction), UV-Vis, SEM-EDX. While the performance of solar cells is measured using a solar simulator. The XRD pattern shows that the sample has a crystal structure of MAPbI3, PbI2, and CuO phases. The MAPbI3 lattice parameter increased with increasing Mg acetate concentration. The grain size of the perovskite layer is between 5 - 15 μm, with a thickness of about 30 μm. The efficiency of perovskite solar cells increases with the increasing concentration of MgAc2 .